Manganese effects on the development and the mineral composition of four tropical forage legumes - Jardim, Lia M. Beatriz F.; Malavolta, E. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1984)
Four tropical forage legumes (Galactia striata. Glycine wightii, Macroptilium atropurpureum and Stylosanthes guianensis), were grown in nutrient solution under varying levels of manganese (0., 25, 50 e 100 ppm). With respect to the differential tolerance between the species, the following was observed: a) Stylosanthes was not affected neither in therms of growth nor in terms of symptons of toxicity. Galactia was realtively less tolerant: its growth was significantly reduced by 100 ppm of Mn in the substrate which also caused severe toxicity symptons. b) Glycine and Macroptilium were sensitive to high Mn. Growth of the former was decreased by 25 ppm, being not further reduced by higher concentrations. The Mn concentration of 50 ppm caused the highest reduction of the growth of Macroptilium. Toxicity symptoms were more acute in the case of Glycine. c) The addition of Mn induced a decrease in the content of K, Ca and Mg. The levels of Cu and Zn in the tops decreased whereas the Mn concentration increased in the whole plant.